Sekar Jagad Art Studio as An Agent of Citizens’s Diplomacy (Study Of Women’s Participation In Intercultural Relations) - Setyasih Harini (Salasika, 2018)
Communication technology could increase opportunities for Indonesians to develop sociocultural relations with people from other countries. Nowadays interrelations of citizens can support government policy. Sekar Jagad art studio is group of women from Sukoharjo regency, central Java who has interest of traditional art and often make international performances. This activity has the purpose to strengthen national identity and national character. The other purpose of this activity is to support diplomacy of government. It is important to promote one of Indonesian culture (Javanese art) in international level. Promoting culture in international performance is one way to increase the positive image of Indonesia. The purpose of this research is to explain how women’s intercultural engagement can be an agent of citizens’ diplomacy. The subjects of the research were the women who are members of Sekar Jagad art studio. As a qualitative project, the data was collected from documentation and interview. The result of this research shows that the women of Sekar Jagad Art Studio promote Javanese culture through international performances. These activities can be seen to represent citizens’ diplomacy and support the diplomatic efforts of the Indonesian government aimed at strengthening relationships with other countries. In summary, this research shows how Sekar Jagad Art Studio as an agent for citizens’ diplomacy has promoted Javanese culture to foreign countries in order to strengthen national identity and promote a positive image of Indonesia.